Removing the Influence of Shimmer in the Calculation of Harmonics-To-Noise Ratios Using Ensemble-Averages in Voice Signals. (2009) - Ferrer Ferrer, Carlos Carlos; González González, Eduardo Eduardo; Hernández-Díaz Hernández-Díaz, María E. María E.; Torres Torres, Diana Diana; del Toro del Toro, Anesto Anesto
Abstract : Harmonics-to-noise ratios (HNRs) are affected by general aperiodicity in voiced speech signals. To specifically reflect a signal-to-additive-noise ratio, the measurement should be insensitive to other periodicity perturbations, like jitter, shimmer, and waveform variability. The ensemble averaging technique is a time-domain method which has been gradually refined in terms of its sensitivity to jitter and waveform variability and required number of pulses. In this paper, shimmer is introduced in the model of the ensemble average, and a formula is derived which allows the reduction of shimmer effects in HNR calculation. The validity of the technique is evaluated using synthetically shimmered signals, and the prerequisites (glottal pulse positions and amplitudes) are obtained by means of fully automated methods. The results demonstrate the feasibility and usefulness of the correction.